Examining the role of product quality in enhancing brand trust and purchase decisions: Evidence from smartphone users in Central Jakarta - Ilham, M Hijri; Rochman, Abdul; Mafthuchach, Viniyati (Privietlab, 2025)
Based on Counterpoint Research data, from quarter 1 of 2022 to quarter 1 of 2023, Xiaomi is the cellphone vendor that has fallen the most, with a decline in market share of 24.8 percent YoY. This study examines the effect of product quality on brand trust and its impact on purchasing decisions for Xiaomi smartphone products in Central Jakarta. The research method used was a survey with data collected through a questionnaire distributed to 170 Xiaomi smartphone users in Central Jakarta. Data analysis was performed using statistical methods, including validity, reliability, and Structural Equation Modeling (SEM) tests with SmartPLS 4.0. The results show that product quality significantly increased brand trust, which had a positive impact on purchasing decisions. These findings suggest that improving product quality can increase consumer trust in the brand, which, in turn, drives higher purchase decisions. This study has several limitations, including focusing only on Xiaomi users in Central Jakarta and not considering other external factors that might influence purchasing decisions. This research helps companies understand how product quality is critical to building brand trust, and how consumers’ purchasing decisions are influenced. These results can be used as a basis for creating better marketing strategies and increasing consumer satisfaction.